2011
DOI: 10.5120/3005-4048
|View full text |Cite
|
Sign up to set email alerts
|

A Two Stage Methodology for Siting and Sizing of DG for Minimum Loss in Radial Distribution System using RCGA

Abstract: This paper presents a new methodology using Real Coded Genetic Algorithm (RCGA) for the placement of Distributed Generators(DG) in the radial distribution systems to reduce the real power losses and to improve the voltage profile. A two-stage methodology is used for the optimal DG placement . In the first stage, single DG placement algorithm is used to find the optimal DG locations and in the second stage, Real Coded Genetic Algorithm is used to find the size of the DGs corresponding to maximum loss reduction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
(16 reference statements)
0
7
0
1
Order By: Relevance
“…In the literature [20][21][22][23][24][25], the authors investigated the problem of deployment of distributed electricity sources to reduce active power losses and improve voltage characteristics. Lalitha et al [20] used the fuzzy artificial immune system to determine the location of distributed sources, to improve the characteristics of voltage and reduce active power losses.…”
Section: Non-traditional Methods For Determining Optimal Location Andmentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature [20][21][22][23][24][25], the authors investigated the problem of deployment of distributed electricity sources to reduce active power losses and improve voltage characteristics. Lalitha et al [20] used the fuzzy artificial immune system to determine the location of distributed sources, to improve the characteristics of voltage and reduce active power losses.…”
Section: Non-traditional Methods For Determining Optimal Location Andmentioning
confidence: 99%
“…In [21] authors determined the optimal location of a distributed generator, using a genetic algorithm, then used a real-coded genetic algorithm to determine the optimal power of distributed generators. By testing it on the IEEE 33 bus test system, the authors showed that the method drastically reduced overall system power losses and significantly improved the characteristics of voltage.…”
Section: Non-traditional Methods For Determining Optimal Location Andmentioning
confidence: 99%
See 2 more Smart Citations
“…These impacts were studied in both normal steady-state condition (line power losses) and abnormal durations (voltage sag losses). In [9], introduced a new methodology employing RCGA for the situation of DG in the radial distribution systems to decrease real power losses and to get better the voltage profile.…”
Section: Introductionmentioning
confidence: 99%